Penerapan Undang-Undang Tindak Pidana Korupsi terhadap Pelaku Tindak Pidana Perbankan pada Bank Sulawesi Utara (Studi Putusan Nomor: 383/PID.B/2011/PN.MDO - Ahmad Yunus (JURNAL RECHTENS, 2017)
The birth of new forms of crime are so complex as non-conventional crime is corruption, banking, money laundering, corporate crime, cybercrime and others is a consequence of the development of science and technology that can generate positive and negative impacts. Relating to corruption cases in Indonesia, legally Manado District Court Decision No. 383 / Pid.B / 2011 / PN.MND interesting to study, especially from the aspect of suitability public prosecutor charges that apply Law No. 31 of 1999 as amended by Law No. 20 of 2001 on Corruption Eradication by defendant Anivolvia Damal, SH who commit criminal acts of corruption at the bank where he works and suitability considerations judges in imposing criminal defendant by Article 14 of Law No. 31 of 1999 as amended by Law No. 20 of 2001 on Corruption Eradication. The problems discussed in this paper there are two: the first related  to  the suitability of  the prosecution  charges that  apply Law No.  31  of  1999  as amended by Law No. 20 Year 2001 on Eradication of Corruption with the actions of the defendant who committed the crime of banking and related conformity second  rationale judges in imposing criminal defendant by Article 14 of Law No. 31 of 1999 as amended by Law No. 20 of 2001 on Corruption Eradication.